Accounting & management : (Harvard Business School Press, 1987)
The book consists of thirteen essays, by leading scholars, on the actual needs and applications of accounting information in modern businesses. It examines how companies such as Weyerhaeuser, Johnson and Johnson, and Hewlett-Packard have designed new control systems and provided new directions for measuring product costs and managerial performance.